Analisis Etika Sistem Informasi pada Kasus Kebocoran Data PDN 2024: Studi Literatur - Adelsiza Zenoni Harianja; Hesly Irawanda Naibaho (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of digital transformation in Indonesia has increased the use of information systems in public services, including through the establishment of the National Data Center (Pusat Data Nasional/PDN). However, the growing dependence on digital technology has also been accompanied by increasing cybersecurity threats. This study aimed to analyze the 2024 PDN data breach case from the perspective of information systems ethics. This study employed a literature review method with a qualitative descriptive approach. The findings indicated that the PDN incident did not only reveal technical weaknesses in cybersecurity but also demonstrated ethical failures, including inadequate data privacy protection, weak protection of data ownership rights, and reduced accessibility of public services. This study concluded that strengthening information system governance, enhancing cybersecurity, and implementing effective data protection are essential to support secure and sustainable digital transformation in Indonesia.